An enhanced nanocomposite catalyst based on MOFs material, preparation method and application
Through nanocomposite catalysts prepared based on MOFs materials, the toxicity and drug resistance of chemotherapy drugs in the treatment of tumors are solved, the effect of efficiently killing cancer cells in the tumor microenvironment is achieved, and the biocompatibility of the drug is improved .
Patent Information
- Application Number
- CN202411709183.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing chemotherapeutic drugs have systemic toxicity, local treatment limitation and drug resistance problems when treating tumors, and the H2O2 content in the tumor microenvironment is not sufficient to effectively kill cancer cells.
Using a reinforced nanocomposite catalyst based on MOFs materials, the Cu/ZIF/Ca/P structure is formed through the coordination of copper ions and zinc ions with 2-methylimidazole, combining thiosulfate and calcium salt, and then forming a Cu/ZIF/Ca/P structure through polyethylene Alcohol PEG is wrapped, loaded with CaS2O3 to enhance catalytic activity.
This nanocomposite catalyst can rapidly strengthen the Cu(II)/Cu(I) cycle in the tumor microenvironment, maintain a high degradation rate, generate·OH, change cell membrane permeability, prevent Ca2+ outflow, lead to calcium overload and oxidative stress, Coordinately kills tumor cells while improving biocompatibility.
Smart Images

Figure CN119185242B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to an enhanced nano composite catalyst based on MOFs material, a preparation method and application thereof. Background Art
[0002] At present, the traditional medical treatments for tumors are mainly chemotherapy, radiotherapy and surgery. Chemotherapy is prone to cause systemic toxicity and drug resistance, radiotherapy can only treat local tumors, and surgical resection can only be used for early-stage cancer patients, and there is a risk of recurrence. Therefore, it is necessary to find a method with low risk and high efficacy.
[0003] Chemodynamic therapy (CDT) uses transition metal nanomaterials as catalysts to respond in the microacidic environment (TME) unique to tumors. Fenton reaction or Fenton-like reaction is the key step of CDT. In these reactions, transition metal ions catalyze H 2 O 2 Decomposition produces highly reactive oxygen species (ROS), which are strong oxidants that can damage cell membranes, proteins, and DNA, leading to tumor cell death. 2 O 2 The content and acidity of ·OH are higher than those of normal tissues, but it may still not be enough to produce enough ·OH to effectively kill cancer cells. And the current chemotherapy drugs are not very effective. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides an enhanced nano composite catalyst based on MOFs material, a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps:
[0007] Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying;
[0008] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS 2 O 3 ;
[0009] Step 3: The Cu / ZIF solution obtained in step 1 and the CaS 2 O 3 The solution is fully mixed, polyethylene glycol PEG is added and mixed thoroughly to obtain the desired nanocomposite catalyst; wherein Cu / ZIF, CaS 2 O 3 The mass ratio of PEG to PEG is 1:3:5.
[0010] Furthermore, in step 1, the molar ratio of copper ions to zinc ions is 1:4-5; the molar ratio of metal ions to 2-methylimidazole is 0.154-0.2:1; wherein the metal ions are copper ions and zinc ions.
[0011] Furthermore, in step 1, the copper ions and zinc ions as metal sources coordinate with 2-methylimidazole as follows:
[0012] Cu(NO 3 ) 2 ∙3H 2 O and Zn(NO 3 ) 2 ∙6H 2 O, respectively dissolved in solvent to obtain Cu(NO 3 ) 2 ∙3H 2 O solution and Zn(NO 3 ) 2 ∙6H 2 O solution;
[0013] Cu(NO 3 ) 2 ∙3H 2 O solution and Zn(NO 3 ) 2 ∙6H 2 O solution was added with 2-methylimidazole solution under stirring; after thorough mixing, the reaction was carried out; wherein Cu(NO 3 ) 2 ∙3H 2 O solution and Zn(NO 3 ) 2 ∙6H 2 The addition rate of O solution was 7 mL / min.
[0014] Furthermore, the Cu(NO 3 ) 2 ∙3H 2 O solution and Zn(NO 3 ) 2 ∙6H 2 The stirring speed was 500-600 r / min during the addition of O solution to 2-methylimidazole solution. After 2 h of reaction, the speed was adjusted to 200-300 r / min and the reaction was continued for 22 h.
[0015] Further, the replacement reaction process in step 2 is as follows:
[0016] Will Na 2 S 2 O 3The solution is added to the acid solution to fully react;
[0017] Add CaCl to the solution after the reaction 2 , CaS can be obtained by sufficient reaction 2 O 3 ; Among them, Na 2 S 2 O 3 and CaCl 2 The molar ratio is 1 to 1.2:1.
[0018] Furthermore, the acid is hydrochloric acid, Na 2 S 2 O 3 The molar ratio of HCI to HCl was 1:1; the reaction was carried out in a nitrogen atmosphere and in an ice bath.
[0019] Further, the reaction process of step 3 is as follows:
[0020] Cu / ZIF solution and CaS 2 O 3 The solution was stirred and mixed thoroughly, and then PEG was added and stirred continuously. After the reaction was completed, the solution was centrifuged at 11,000 rpm for 10 min, and the step of adding PEG was repeated. The desired nanocomposite catalyst was obtained after freeze drying.
[0021] An enhanced nanocomposite catalyst based on MOFs material, wherein the nanocomposite catalyst is a mesoporous structure, a metal organic framework structure composed of zinc and copper elements as metal connection points is a skeleton, the surface is coated with PEG, and the mesoporous channels are loaded with CaS 2 O 3 .
[0022] An application of an enhanced nanocomposite catalyst based on MOFs material, and application of the nanocomposite catalyst in the preparation of chemotherapy drugs for treating tumors.
[0023] Furthermore, the nanocomposite catalyst is used as a tumor-targeted chemotherapy drug carrier.
[0024] The beneficial effects of the present invention are:
[0025] (1) S in the nanocomposite catalyst obtained in the present invention 2 O 3 2- It can rapidly enhance the circulation of Cu(II) / Cu(I), maintain a high degradation rate in the pH range of 3.0-10.0, and can play a role in the tumor microenvironment;
[0026] (2) The nanocomposite catalyst obtained by the present invention can produce ·OH, which can change the cell membrane permeability so that the expression of PMCA, an ion transporter protein in tumor cells, is restricted, thereby preventing Ca 2+ transported out of tumor cells, causing abnormalities in the ion regulation mechanism in tumor cells, leading to intracellular Ca 2+ Excessive accumulation of calcium causes calcium overload, forming a synergistic effect of CDT and calcium death;
[0027] (2) The nanocomposite catalyst in the present invention is encapsulated by PEG, which reduces its release during transportation and improves the biocompatibility of the nanocomposite catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are the SEM and TEM images of the materials obtained in Comparative Examples 1, 3 and Example 1 of the present invention, a is the SEM of the material obtained in Comparative Example 1, b is the SEM of the material obtained in Comparative Example 3, c is the SEM of the catalyst obtained in Example 1, d is the TEM of the catalyst obtained in Example 1, and e is the TEM and elemental mapping of the material obtained in Step 1 of Example 1.
[0029] Figure 2 These are the BET and pore size curves of the materials obtained in Comparative Examples 2 and 3 of the present invention, where a is the result of the material obtained in Comparative Example 2, and b is the result of the material obtained in Comparative Example 3.
[0030] Figure 3 The infrared absorption spectra of the materials and PET obtained in Comparative Examples 1, 2 and Example 1 of the present invention.
[0031] Figure 4 The materials obtained in Comparative Examples 1, 2, and 3 of the present invention and CaS 2 O 3 X-ray diffraction spectrum of .
[0032] Figure 5 It is the Zeta potential diagram of the materials obtained in Comparative Examples 1, 2, 3 and Example 1 of the present invention.
[0033] Figure 6 This is the X-ray photoelectron spectrum of the material obtained in Comparative Example 3 of the present invention, a is the full XPS spectrum obtained by Cu / ZIF / Ca measurement, b is the Zn element spectrum, c is the Cu element spectrum, d is the Ca element spectrum, and e is the S element spectrum.
[0034] Figure 7 The catalyst Cu / ZIF / Ca and H 2 O 2 The results were measured by cyclic voltammetry after the reaction.
[0035] Figure 8These are the catalytic performance results of the materials obtained in Comparative Examples 2 and 3 of the present invention, a is the result of Comparative Examples 2 and 3 at a pH of 7.4, b is the result of Comparative Examples 2 and 3 at a pH of 5.0, and c is the result of Comparative Example 3 at different reaction times at a pH of 5.0.
[0036] Fig. 9 It is the UV-visible absorption spectrum of the material obtained in the comparative example of the present invention.
[0037] Fig.10 The materials and CaS obtained in each step of Comparative Example 1 and Example 1 of the present invention 2 O 3 The ability to generate ·OH, a is the result when pH is 7.4, b is the result when pH is 5.0 and there is 3% H 2 O 2 The result of existence,
[0038] Fig.11 These are the fluorescence staining results after co-incubation of tumor cells with the materials obtained in Comparative Examples 1, 2, 3 and Example 1 of the present invention, a is the DCFA-DA fluorescence detection result, b is the C11-BODIPY581 / 589 fluorescence probe detection result, and c is the AM, PI and combined use test results.
[0039] Fig.12 FIG. 1 is a biological transmission electron microscopy image of the catalyst obtained in Example 1 of the present invention after being co-incubated with tumor cells for 12 h, and FIG. b is an enlarged view of FIG. a.
[0040] Fig.13 These are the Alizarin Red S staining results after the materials obtained in Comparative Examples 1, 2, 3 and Example 1 of the present invention were co-incubated with tumor cells for 6 h, where Ⅰ is PBS buffer solution, Ⅱ is Comparative Example 1, Ⅲ is Comparative Example 2, Ⅳ is Comparative Example 3, and Ⅴ is Example 1. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0042] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps:
[0043] Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying;
[0044] The specific process is as follows:
[0045] Cu(NO 3 ) 2 ∙3H 2 O and Zn(NO 3 ) 2∙6H 2 O were dissolved in methanol and ultrasonically shaken until completely dissolved to obtain Cu(NO 3 ) 2 ∙3H 2 O solution and Zn(NO 3 ) 2 ∙6H 2 O solution;
[0046] Dissolve 2-methylimidazole in methanol and ultrasonically shake until it is completely dissolved to obtain a 2-methylimidazole solution, which is then placed on a magnetic stirrer. 3 ) 2 ∙3H 2 O solution and Zn(NO 3 ) 2 ∙6H 2 O solution was added to the 2-methylimidazole solution at a speed of 7 mL / min. The solution was stirred at a speed of 600 r / min for 2 h, and the solution gradually changed from light blue to dark blue to obtain the reacted solution. After 2 h, the speed was adjusted to 200-300 r / min and the reaction was continued for 22 h. The final product was centrifuged at a speed of 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried under vacuum at 60 °C for 24 h to obtain Cu / ZIF.
[0047] Among them, Zn(NO 3 ) 2 ∙6H 2 O and Cu(NO 3 ) 2 ∙3H 2 The molar ratio of zinc source to copper source is 4 to 5: 1, and the ratio of zinc source to copper source is not less than 4: 1. Since copper is difficult to coordinate with 2-methylimidazole, zinc can only be used as a skeleton to partially replace zinc with copper. The organic metal skeleton is difficult to form below this ratio. The molar ratio of the total amount of zinc source and copper source to 2-methylimidazole is 0.154 to 0.2: 1.
[0048] In the above process, the feeding speed needs to be controlled. Too fast a feeding speed can easily lead to cluster formation. Rapid stirring is conducive to the formation of smaller crystal nuclei, so that the final material particle size is smaller.
[0049] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS 2 O 3 ;
[0050] The reaction process is as follows:
[0051] Will Na 2 S 2 O 3 Soluble in H 2O was completely dissolved by ultrasonic vibration to obtain Na 2 S 2 O 3 Solution, in Na 2 S 2 O 3 Dilute hydrochloric acid was added to the solution and the reaction was continued for 2 h to obtain the post-reaction solution. During the reaction, nitrogen was maintained throughout the process and the ice-water bath environment was maintained. 2 O 3 2- In a high-temperature air environment, it will decompose into elemental sulfur and sulfur dioxide. Elemental sulfur will usually precipitate out in the form of a yellow solid, while sulfur dioxide will escape in the form of gas, so the external environment needs to be kept stable.
[0052] After the reaction, the solution was filtered and mixed with CaCl 2 The reaction was carried out in a corrosion-resistant reaction vessel for 5 h, and the solution was freeze-dried for 24 h to obtain CaS 2 O 3 During the above reaction, nitrogen was maintained throughout the process and the ice water bath environment was maintained. 2 O 3 The solubility can be increased at low temperatures.
[0053] Step 3: The Cu / ZIF solution obtained in step 1 and the CaS 2 O 3 The solution is fully mixed, polyethylene glycol PEG is added and mixed thoroughly to obtain the desired nanocomposite catalyst; wherein Cu / ZIF, CaS 2 O 3 The mass ratio of PEG to PEG is 1:3:5.
[0054] The specific reaction process is as follows:
[0055] Cu / ZIF and RO water were mixed and ultrasonically dispersed, and then stirred for 5 min at a speed of 200-300 r / min to obtain a Cu / ZIF solution. The Cu / ZIF solution was placed in a vacuum drying oven and vacuumed for 20 min to remove the air in the Cu / ZIF pores. Since Cu / ZIF has a large specific surface area and too many pores, the amount of air in it is too high. Vacuuming can extract the air in it, increase the pressure and make CaS 2 O 3 Easier to load.
[0056] 6 g of CaS 2 O 3 Dispersed in 50 mL of water and ultrasonically dispersed for 5 min to obtain CaS 2 O 3 Solution; Cu / ZIF solution and CaS after vacuum 2 O3 The solution was mixed and stirred at a speed of 300 r / min for 20 min to obtain a mixed solution. 10 g PEG was added to the mixed solution, and mixed and stirred at a speed of 300 r / min for 1 h. Centrifugation was performed at a speed of 11000 rpm for 10 min, and PEG was added twice, stirred, centrifuged, and freeze-dried to obtain Cu / ZIF / Ca / P. Cu / ZIF:CaS 2 O 3 :PEG mass ratio is 1:3:5, ensuring CaS 2 O 3 loading and effective encapsulation of PEG.
[0057] Example 1
[0058] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps:
[0059] Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying;
[0060] 0.25 g of Cu(NO 3 ) 2 ∙3H 2 O and 1.53 g Zn(NO 3 ) 2 ∙6H 2 O were dissolved in 70 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0061] 3.3 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 500 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0062] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0063] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS 2 O 3 ;
[0064] 3.95 g of Na 2 S 2 O3 Dissolve in 46 mL H 2 O in a vacuum oven until the solution is completely dissolved, and then the solution E is obtained. During this process, nitrogen is passed through the solution to remove oxygen and the solution is kept in an ice-water bath. 2 S 2 O 3 After complete dissolution, add 25 mL of 0.5 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. The nitrogen flow and ice water bath environment are still maintained. After 2 h, the reaction solution is filtered and mixed with 2.7 g of CaCl 2 The reaction was carried out in a corrosion-resistant reaction vessel for 5 h to obtain solution G, which was then freeze-dried for 24 h to obtain CaS 2 O 3 .
[0065] Step 3: The Cu / ZIF solution obtained in step 1 and the CaS 2 O 3 The solution is fully mixed, polyethylene glycol PEG is added and mixed thoroughly to obtain the desired nanocomposite catalyst; wherein Cu / ZIF, CaS 2 O 3 The mass ratio of PEG to PEG is 1:3:5.
[0066] 1.5 g of Cu / ZIF obtained in step 1 was dissolved in 50 mL of RO water and mixed and ultrasonically dispersed at 300 r / min for 5 min to obtain H solution. The H solution was placed in a vacuum oven and evacuated for 20 min to remove the air in the pores. 4.5 g of CaS 2 O 3 Disperse in 50 mL of water and perform ultrasonic dispersion for 5 min to obtain solution I. Stir the vacuumized solution H and solution I at 300 r / min for 20 min to obtain solution J.
[0067] 7.5 g of PEG was dissolved in solution J and stirred at 300 r / min for 1 h to obtain solution K. The solution was centrifuged at 11000 rpm for 10 min. PEG was added twice and then freeze-dried for 24 h to obtain Cu / ZIF / Ca / P (Cu / ZIF-8@CaS in the figure). 2 O 3 @PEG).
[0068] Example 2
[0069] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps:
[0070] Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying;
[0071] 0.25 g of Cu(NO 3 ) 2 ∙3H 2 O and 1.47 g Zn(NO 3 ) 2 ∙6H 2 O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0072] 2.9 g of 2-methylimidazole was dissolved in 60 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0073] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0074] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS 2 O 3 ;
[0075] 3.95 g of Na 2 S 2 O 3 Dissolve in 46 mL H 2 O in a vacuum oven until the solution is completely dissolved, and then the solution E is obtained. During this process, nitrogen is passed through the solution to remove oxygen and the solution is kept in an ice-water bath. 2 S 2 O 3 After complete dissolution, add 25 mL of 0.5 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. The nitrogen flow and ice water bath environment are still maintained. After 2 h, the reaction solution is filtered and mixed with 2.91 g of CaCl 2 The reaction was carried out in a corrosion-resistant reaction vessel for 5 h to obtain solution G, which was then freeze-dried for 24 h to obtain CaS 2 O 3 .
[0076] Step 3: The Cu / ZIF solution obtained in step 1 and the CaS 2 O 3 The solution is fully mixed, polyethylene glycol PEG is added and mixed thoroughly to obtain the desired nanocomposite catalyst; wherein Cu / ZIF, CaS 2O 3 The mass ratio of PEG to PEG is 1:3:5.
[0077] 1.5 g of Cu / ZIF obtained in step 1 was dissolved in 50 mL of RO water and mixed and ultrasonically dispersed at 300 r / min for 5 min to obtain H solution. The H solution was placed in a vacuum oven and evacuated for 20 min to remove the air in the pores. 4.5 g of CaS 2 O 3 Disperse in 50 mL of water and perform ultrasonic dispersion for 5 min to obtain solution I. Stir the vacuumized solution H and solution I at 300 r / min for 20 min to obtain solution J.
[0078] 7.5 g of PEG was dissolved in J solution and stirred at 300 r / min for 1 h to obtain K solution. The solution was centrifuged at 11000 rpm for 10 min, and PEG was added twice and freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0079] Example 3
[0080] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps:
[0081] Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying;
[0082] 0.25 g of Cu(NO 3 ) 2 ∙3H 2 O and 1.43 g Zn(NO 3 ) 2 ∙6H 2 O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0083] 2.7 g of 2-methylimidazole was dissolved in 60 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0084] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0085] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS 2 O 3 ;
[0086] 3.95 g of Na 2 S 2 O 3 Dissolve in 46 mL H 2 O in a vacuum oven until the solution is completely dissolved, and then the solution E is obtained. During this process, nitrogen is passed through the solution to remove oxygen and the solution is kept in an ice-water bath. 2 S 2 O 3 After complete dissolution, add 25 mL of 0.5 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. The nitrogen flow and ice water bath environment are still maintained. After 2 h, the reaction solution is filtered and mixed with 3.05 g of CaCl 2 The reaction was carried out in a corrosion-resistant reaction vessel for 5 h to obtain solution G, which was then freeze-dried for 24 h to obtain CaS 2 O 3 .
[0087] Step 3: The Cu / ZIF solution obtained in step 1 and the CaS 2 O 3 The solution is fully mixed, polyethylene glycol PEG is added and mixed thoroughly to obtain the desired nanocomposite catalyst; wherein Cu / ZIF, CaS 2 O 3 The mass ratio of PEG to PEG is 1:3:5.
[0088] 1.5 g of Cu / ZIF obtained in step 1 was dissolved in 50 mL of RO water and mixed and ultrasonically dispersed at 300 r / min for 5 min to obtain H solution. The H solution was placed in a vacuum oven and evacuated for 20 min to remove the air in the pores. 4.5 g of CaS 2 O 3 Disperse in 50 mL of water and perform ultrasonic dispersion for 5 min to obtain solution I. Stir the vacuumized solution H and solution I at 300 r / min for 20 min to obtain solution J.
[0089] 7.5 g of PEG was dissolved in J solution and stirred at 300 r / min for 1 h to obtain K solution. The solution was centrifuged at 11000 rpm for 10 min, and PEG was added twice and freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0090] Example 4
[0091] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps:
[0092] Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying;
[0093] 0.25 g of Cu(NO 3 ) 2 ∙3H 2 O and 1.37 g Zn(NO 3 ) 2 ∙6H 2 O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0094] 2.4 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0095] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0096] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS 2 O 3 ;
[0097] 3.16 g of Na 2 S 2 O 3 Dissolve in 46 mL H 2 O in a vacuum oven until the solution is completely dissolved, and then the solution E is obtained. During this process, nitrogen is passed through the solution to remove oxygen and the solution is kept in an ice-water bath. 2 S 2 O 3 After complete dissolution, add 25 mL of 0.4 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. The nitrogen flow and ice water bath environment are still maintained. After 2 h, the reaction solution is filtered and mixed with 2.55 g of CaCl 2 The reaction was carried out in a corrosion-resistant reaction vessel for 5 h to obtain solution G, which was then freeze-dried for 24 h to obtain CaS 2 O 3 .
[0098] Step 3: The Cu / ZIF solution obtained in step 1 and the CaS 2 O 3 The solution is fully mixed, polyethylene glycol PEG is added and mixed thoroughly to obtain the desired nanocomposite catalyst; wherein Cu / ZIF, CaS 2 O 3 The mass ratio of PEG to PEG is 1:3:5.
[0099] 2 g of Cu / ZIF obtained in step 1 was dissolved in 50 mL of RO water and mixed and ultrasonically dispersed at 300 r / min for 5 min to obtain H solution. The H solution was placed in a vacuum drying oven and evacuated for 20 min to remove the air in the pores. 6 g of CaS 2 O 3 Disperse in 50 mL of water and disperse by ultrasonic for 5 min to obtain solution I. Stir the vacuumized solution H and solution I at 300 r / min for 20 min to obtain solution J.
[0100] 10 g of PEG was dissolved in solution J and stirred at 300 r / min for 1 h to obtain solution K. The solution K was centrifuged at 11000 rpm for 10 min. After adding PEG twice, the solution was freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0101] Example 5
[0102] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps:
[0103] Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying;
[0104] 0.2 g of Cu(NO 3 ) 2 ∙3H 2 O and 1.02 g Zn(NO 3 ) 2 ∙6H 2 O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0105] 1.7 g of 2-methylimidazole was dissolved in 60 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0106] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0107] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS 2 O 3 ;
[0108] 3.16 g of Na 2 S 2 O 3 Dissolved in 47 mL H 2 O in a vacuum oven until the solution is completely dissolved, and then the solution E is obtained. During this process, nitrogen is passed through the solution to remove oxygen and the solution is kept in an ice-water bath. 2 S 2 O 3 After complete dissolution, add 25 mL of 0.4 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. The nitrogen flow and ice water bath environment are still maintained. After 2 h, the reaction solution is filtered and mixed with 2.66 g of CaCl 2 The reaction was carried out in a corrosion-resistant reaction vessel for 5 h to obtain solution G, which was then freeze-dried for 24 h to obtain CaS 2 O 3 .
[0109] Step 3: The Cu / ZIF solution obtained in step 1 and the CaS 2 O 3 The solution is fully mixed, polyethylene glycol PEG is added and mixed thoroughly to obtain the desired nanocomposite catalyst; wherein Cu / ZIF, CaS 2 O 3 The mass ratio of PEG to PEG is 1:3:5.
[0110] 2 g of Cu / ZIF obtained in step 1 was dissolved in 50 mL of RO water and mixed and ultrasonically dispersed at 300 r / min for 5 min to obtain H solution. The H solution was placed in a vacuum drying oven and evacuated for 20 min to remove the air in the pores. 6 g of CaS 2 O 3 Disperse in 50 mL of water and perform ultrasonic dispersion for 5 min to obtain solution I. Stir the vacuumized solution H and solution I at 300 r / min for 20 min to obtain solution J.
[0111] 10 g of PEG was dissolved in solution J and stirred at 300 r / min for 1 h to obtain solution K. The solution K was centrifuged at 11000 rpm for 10 min. After adding PEG twice, the solution was freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0112] Comparative Example 1
[0113] In order to illustrate the beneficial effects of the present invention, a comparative example is set, with ZIF-8MOF material as a comparison, and the specific preparation method is as follows:
[0114] 1.5 g of zinc nitrate hexahydrate was dissolved in 70 mL of methanol and ultrasonically dispersed until completely dissolved to obtain solution L. In addition, 3.3 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically dispersed until completely dissolved to obtain solution M. The L solution was slowly added into the M solution and turned milky white. After stirring at 500 r / min at room temperature for 2 h, the speed was adjusted to 200 r / min and the reaction was continued for 22 h. Finally, it was centrifuged and washed three times with methanol and water, and dried in a vacuum at 60 °C for 12 h to obtain ZIF-8.
[0115] Comparative Example 2
[0116] The comparative example preparation method is as follows:
[0117] 0.3 g of Cu(NO 3 ) 2 ∙3H 2 O and 1.91 g of Zn(NO 3 ) 2 ∙6H 2 O were dissolved in 70 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0118] 3.06 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 500 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0119] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF (Cu / ZIF-8).
[0120] Comparative Example 3
[0121] The comparative example preparation method is as follows:
[0122] 5 g of Na 2 S 2 O 3 Dissolve in 45 mL H 2 O in a vacuum oven until the solution is completely dissolved, and then the solution E is obtained. During this process, nitrogen is passed through the solution to remove oxygen and the solution is kept in an ice-water bath. 2 S 2 O 3 After complete dissolution, add 25 mL of 0.5 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. The nitrogen flow and ice water bath environment are still maintained. After 2 h, the reaction solution is filtered and mixed with 2.7 g of CaCl 2 The reaction was carried out in a corrosion-resistant reaction vessel for 5 h to obtain solution G, which was then freeze-dried for 24 h to obtain CaS 2 O 3 .
[0123] 2 g of Cu / ZIF obtained in Example 1 was dissolved in 50 mL of RO water and mixed and ultrasonically dispersed at a speed of 300 r / min and stirred for 5 min to obtain H solution. The H solution was placed in a vacuum drying oven and evacuated for 20 min to remove the air in the pores. 4 g of CaS 2 O 3 Dispersed in 50 mL of water and ultrasonically dispersed for 5 min to obtain solution I. The vacuumized solution H and solution I were stirred at 300 r / min for 20 min to obtain solution J. After centrifugation at 11000 rpm for 10 min, the solid was freeze-dried for 24 h to obtain Cu / ZIF / Ca (Cu / ZIF-8@CaS 2 O 3 ).
[0124] The effects of the present invention are described below through test results.
[0125] Figure 1 The SEM and TME images of the materials obtained in the comparative example and embodiment 1 are shown in FIG. Figure 1 It can be seen that the ZIF-8 obtained in Comparative Example 1 has a relatively clear regular dodecahedron structure and is suitable for a series of applications such as energy storage and drug delivery. Figure 1 As can be seen in b, the load CaS 2 O 3 The Cu / ZIF / Ca morphology did not change significantly after treatment. Figure 1 As can be seen in Figure c, the surface roughness of Cu / ZIF / Ca / P increases after being coated with PEG. Figure 1 As can be seen in d, Cu / ZIF / Ca / P has CaS 2 O 3From its elemental mapping diagram, it can be seen that Cu / ZIF is a metal organic framework structure in which zinc and copper elements are used as metal connection points at the same time.
[0126] Figure 2 The BET and pore size curves of Comparative Examples 2 and 3 are shown in the figure. 2 O 3 The specific surface area of Cu / ZIF reached 1354 m 2 / g, loaded with CaS 2 O 3 The specific surface area of Cu / ZIF / Ca is 310 m 2 / g, it can be seen from the results that CaS 2 O 3 Effective loading in Cu / ZIF.
[0127] Figure 3 The infrared absorption spectra of Comparative Examples 1 and 2 and Example 1 and PEG are shown in the figure. It can be seen from the figure that the infrared spectra of ZIF-8, Cu / ZIF, and Cu / ZIF / Ca / P are basically the same, with 1584 cm -1 The stretching vibration of C=N group is at 1251 cm -1 ) and CH(2876 cm -1 ) Two characteristic peaks indicate the successful encapsulation of PEG.
[0128] Figure 4 For comparative examples 1, 2, 3 and CaS 2 O 3 (prepared by the method in step 2 of any embodiment) is shown in the X-ray diffraction spectrum. It can be seen from the figure that the crystal structures of Cu / ZIF and Cu / ZIF / Ca are basically the same as ZIF-8, and the characteristic absorption peak intensity of Cu / ZIF is much higher than that of ZIF-8, which proves that the crystallinity of Cu / ZIF is higher than that of ZIF-8, while the characteristic absorption peak intensity of Cu / ZIF / Ca is much lower, indicating that the crystallinity is lowered. This is due to the fact that CaS 2 O 3 Some of them remained on the surface of Cu / ZIF, and CaS was detected in Cu / ZIF / Ca. 2 O 3 The characteristic peaks of CaS 2 O 3 of successful load.
[0129] Figure 5The Zeta potential diagram of the materials obtained in Comparative Examples 1, 2, 3 and Example 1 shows that due to the addition of excess 2-methylimidazole when preparing the MOF material, its strong electronegativity and the coordination of zinc and copper present a higher potential. The encapsulation of PEG greatly reduces the potential of Cu / ZIF / Ca / P, and the negative potential can promote the circulation of nanomaterials in the blood, making the nanomaterials more efficient in entering tumor cells.
[0130] Figure 6 The X-ray photoelectron spectrum of the material obtained in Comparative Example 3 shows that the peaks of Zn, Cu, Ca, O, C, N, and S appear in the spectrum of Cu / ZIF / Ca, and the peaks of Zn 2p appear in the spectrum of Zn 2+ (1021.78, 1044.63eV) and Cu 2+ The signal peaks at 932.48 and 952.13 eV indicate that the valence state of Zn and Cu elements in Cu / ZIF is in a divalent state. The two characteristic peaks of Ca 2p at 347.08 eV and 350.73 eV and the two characteristic peaks of S 2p at 163.58 eV and 167.28 eV confirm that CaS 2 O 3 Compared with the TEM images, it is proved that CaS 2 O 3 It exists both on the surface and inside of Cu / ZIF.
[0131] Figure 7 Cyclic voltammetry was used to measure the relationship between Cu / ZIF and S 2 O 3 2- and H 2 O 2 The reaction image shows that in the absence of glutathione, the Cu + With Cu 2+ Being able to achieve a good cycle proves that S 2 O 3 2- Enhanced success of Fenton-like reactions.
[0132] Figure 8 The catalytic performance results of Comparative Examples 1 and 3 are shown in Figure 2. 2 O 2 ESR tests of Cu / ZIF and Cu / ZIF / Ca were performed under different pH and time conditions. As can be seen from the figure, a is that Cu / ZIF does not have ∙OH signal within 0-5min, proving that Cu / ZIF in this environment cannot catalyze H 2 O 2Produce ∙OH. Under the condition of pH 7.4, Cu / ZIF / Ca produced a relatively strong 1:2:2:1 characteristic peak within 0-5min, which was a unique signal after ∙OH combined with 5,5-dimethyl-1-pyrroline-N-oxide (DMPO).
[0133] from Figure 8 As can be seen in Figure b, the signal peak generated by Cu / ZIF in 0-5min is higher than that of Cu / ZIF / Ca, which may be due to the presence of Cu(Ⅲ) which hinders the binding of DMPO with ∙OH. Figure 8 As can be seen in Figure c, under pH 5.0, the signal peak of ∙OH generated by adding Cu / ZIF / Ca within 0-20 min first increased and then decreased, which proves that the binding of DMPO with ∙OH is hindered. In order to further verify Cu(Ⅲ), periodate was used as a scavenger for Cu(Ⅲ), making it show an ultraviolet absorption peak at 340nm.
[0134] Fig. 9 The pH is 5.0 and H 2 O 2 Under the conditions of , the capture of Cu(Ⅲ) can be seen from the figure that Cu / ZIF does not cause the change of the peak shape at 340nm. 2 O 3 Afterwards, a more obvious red shift appeared, proving the possibility of the existence of Cu(Ⅲ).
[0135] Fig.10 is the ability of the nanocatalyst to generate ·OH under different pH conditions. 3'3'5'5'-tetramethylbenzidine (TMB) was used to react with comparative examples 1, 2, and 3. TMB is colorless and transparent when dissolved in DMSO. Strong oxidizing ROS can oxidize TMB to generate a group with a blue conjugated structure. Its unique absorption peak at 652 nm can be detected using an ultraviolet spectrophotometer (UV-vis). Fig.10 a represents the concentration of Cu / ZIF / Ca, Cu / ZIF, CaS at 200 µg / mL 2 O 3 , ZIF-8 were added to 3% H 2 O 2 The absorption peak at 650 nm was detected in the solution. The results showed that only Cu / ZIF / Ca could make TMB produce a strong peak at 650 nm, which was consistent with the ESR test results, proving that S 2 O 3 2- It can expand the pH limit range of Fenton-like reactions. Fig.10 b is at pH 5.0 and 3% H 2 O2 In the presence of 2 O 3 , ZIF-8, the results show that the ∙OH signal peak generated by Cu / ZIF / Ca is higher than that of Cu / ZIF, further proving that S 2 O 3 2- Effect as an enhancer of Fenton-like reactions.
[0136] In order to illustrate the effect of the catalyst obtained by the present invention on tumors, the materials obtained in Comparative Examples 1, 2, 3 and Example 1 were co-incubated with tumor cells for 6 h, and DCFH-DA was used to detect reactive oxygen species (ROS) and nitric oxide (NO) and determine the overall degree of oxidative stress. The intracellular ∙OH can oxidize non-fluorescent DCFH to generate fluorescent DCF. The results are shown in FIG. Fig.11 shown. Fig.11 Figure a is the test result of the DCFA-DA probe. It can be seen that when the concentration of Cu / ZIF / Ca / P is 50 µg / mL, the most ROS can be detected, proving that the catalyst obtained by the present invention has a relatively good catalytic effect.
[0137] Fig.11 Figure b is the test result of C11-BODIPY581 / 589 ratio fluorescence probe. From the figure, we can see that the fluorescence changes of LPO membranes stimulated by different materials can be detected to detect the fluorescence of LPO membranes and the effect of lipid peroxidation. Similarly, more fluorescence can be detected in the Cu / ZIF / Ca / P group, which indicates that more ∙OH can be produced in the Cu / ZIF / Ca / P group to oxidize the cell membrane and make it show corresponding fluorescence changes. Fig.11 Figure c is the test result of AM, PI and their combination. Because their combination can only pass through the disordered area of the dead cell membrane to reach the cell nucleus, embed into the DNA double helix area of the cell, and produce fluorescence, only staining dead cells, which can more intuitively show the killing ability of the material on tumor cells. It can be seen from the figure that Cu / ZIF, Cu / ZIF / Ca, and Cu / ZIF / Ca / P can kill tumor cells, and there are almost no living cells in Cu / ZIF / Ca and Cu / ZIF / Ca / P, indicating that CaS 2 O 3 Encapsulation with PEG can increase the catalytic effect and drug encapsulation rate of the nanocatalyst to a greater extent.
[0138] Fig.12This is a biological transmission electron microscope image of the catalyst obtained in Example 1 of the present invention after co-incubation with tumor cells for 12 hours. It can be seen from the figure that the cell morphology is obviously abnormal; most mitochondria in the cytoplasm have swollen, and the mitochondria are round, oval or long strips, the cristae structure is dissolved and broken, the matrix is lost, local vacuolation occurs, and the outer membrane is continuous and intact; the rough endoplasmic reticulum is expanded. This is due to the Zn 2+ Ion disorder and Ca in tumor cells 2+ Caused by overloading.
[0139] Fig.13 The Alizarin Red S staining images after co-incubation with tumor cells in Comparative Examples 1, 2, 3 and Example 1 of the present invention are shown. The Alizarin Red S calcium staining method is an authoritative and classic technical method that aims to analyze the orange-red calcium deposition phenomenon in fixed cell samples by using chelation technology to produce a complex between calcium ions and Alizarin Red S. As can be seen from the figure, orange-red calcium deposition appears in Cu / ZIF / Ca and Cu / ZIF / Ca / P, proving that Ca 2+ Successfully distributed in tumor cells.
[0140] The Cu / ZIF / Ca / P prepared by the present invention can be used as a carrier to load other chemotherapeutic drugs, and can also be directly used as a chemotherapeutic drug.
[0141] The present invention uses PEG to wrap Cu / ZIF and load CaS 2 O 3 , Cu / ZIF / Ca / P is obtained. The Cu / ZIF prepared by the present invention is a nano-carrier with small particle size, large specific surface area and high crystallinity. CaS 2 O 3 The introduction of can greatly enhance the efficiency of chemodynamic therapy, and on the other hand, the excessive ∙OH produced can inhibit the Ca 2+ The expression of efflux proteins also causes mitochondrial calcium overload in tumor cells, which in turn promotes apoptosis of cancer cells through oxidative stress. 2 O 3 Used to enhance chemodynamic therapy and calcium death synergistic therapy, it provides new construction ideas and treatment models for the design and biomedical applications of new nanocatalysts.
Claims
1. A method for preparing an enhanced nanocomposite catalyst based on MOFs material, characterized in that: The following steps are involved: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:
5.
2. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: In the step 1, the molar ratio of copper ions to zinc ions is 1:4-5; the molar ratio of metal ions to 2-methylimidazole is 0.154-0.2:1; wherein the metal ions are copper ions and zinc ions.
3. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: In the step 1, the coordination process of copper ions and zinc ions as metal sources with 2-methylimidazole is as follows: Dissolve Cu(NO3)2·3H2O and Zn(NO3)2·6H2O in solvents to obtain Cu(NO3)2·3H2O solution and Zn(NO3)2·6H2O solution respectively; Add Cu(NO3)2·3H2O solution and Zn(NO3)2·6H2O solution to 2-methylimidazole solution under stirring conditions; react after sufficient mixing; the addition rate of Cu(NO3)2·3H2O solution and Zn(NO3)2·6H2O solution is 7mL / min.
4. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 3, characterized in that: The stirring speed during the addition of the Cu(NO3)2·3H2O solution and the Zn(NO3)2·6H2O solution to the 2-methylimidazole solution is 500-600 r / min; after reacting for 2 hours, the rotation speed is adjusted to 200-300 r / min and the reaction is continued for 22 hours.
5. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: The replacement reaction process in step 2 is as follows: Add Na2S2O3 solution to the acid solution to fully react; Add CaCl2 to the solution after the reaction and allow it to react sufficiently to obtain CaS2O3; wherein the molar ratio of Na2S2O3 to CaCl2 is 1 to 1.2:
1.
6. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 5, characterized in that: The acid used was hydrochloric acid, and the molar ratio of Na2S2O3 to HCl was 1:1; the reaction process was maintained in a nitrogen-filled and ice-bath environment.
7. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: The reaction process of step 3 is as follows: The Cu / ZIF solution and the CaS2O3 solution were fully stirred and mixed, and then PEG was added and continued to stir. After the reaction was completed, centrifugation was performed at a speed of 11000 rpm for 10 minutes, and the step of adding PEG was repeated. The desired nanocomposite catalyst was obtained after freeze-drying.
8. The enhanced nanocomposite catalyst based on MOFs material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The nano composite catalyst is a mesoporous structure, the metal organic framework structure formed by zinc and copper elements as metal connection points is the skeleton, the surface is wrapped by PEG, and the mesoporous channels are loaded with CaS2O3.
9. The use of the enhanced nanocomposite catalyst based on MOFs material as claimed in claim 8, characterized in that: The nano composite catalyst is used in preparing chemotherapy drugs for treating tumors.
Citation Information
Patent Citations
Preparation method of MOFs nano material supporting nano metal particles
CN108097316A
Preparation method of composite photocatalytic material of Fe3O4-N doped with Ni / Zn-MOFs / g-C3N4
CN108579819A